The ISDS Mechanism and Standards of Protection in the Investment Treaty - Pandu Rizky Putra Pratama; Prita Amalia (University of Jember, 2020)
International investment activities require legal certainty for investors. While the host country also needs legal certainty related to state sovereignty, legal protection is needed for investors and the host country to realize legal certainty in investment activities. Countries in the world entered into investment agreements to provide legal protection for investment activities. In investment agreements, generally, there are requirements to comply with the national law of the host country to get protection from investment agreements. This study aims to review the implications of not fulfilling the obligations in the investment agreement to apply the benefits contained therein, specifically regarding ISDS mechanism and protection standards. This study finds that the impact of the non-fulfillment of these obligations on the ISDS mechanism depends on the admission clause specified in the Bilateral Investment Treaty (BIT). On standards of protection, it refers to general principles of international law and arbitration decisions, investments that violate these obligations do not receive international legal protection. This research suggests the Indonesian Government tighten the admission clause in the BIT to prevent investors from using the ISDS mechanism in the BIT and to specify the impact of violating obligations to comply with the national laws of the host country. KEYWORDS: International Investment Law, Standards of Protection, Bilateral Investment Treaty